2019
DOI: 10.1051/parasite/2019011
|View full text |Cite
|
Sign up to set email alerts
|

MALDI-TOF mass spectrometry: a new tool for rapid identification of cercariae (Trematoda, Digenea)

Abstract: Identification of cercariae was long based on morphological and morphometric features, but these approaches remain difficult to implement and require skills that have now become rare. Molecular tools have become the reference even though they remain relatively time-consuming and expensive. We propose a new approach for the identification of cercariae using MALDI-TOF mass spectrometry. Snails of different genera (Radix, Lymnaea, Stagnicola, Planorbis, and Anisus) were collected in the field to perform emitting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 30 publications
3
34
1
Order By: Relevance
“…Regarding the ITS2 fragment, our isolates presented the highest similarity with sequences of Australapatemon sp. (MK168687 and MK168688) from France [ 25 ]. Based on the COI locus, an isolate of Australapatemon sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the ITS2 fragment, our isolates presented the highest similarity with sequences of Australapatemon sp. (MK168687 and MK168688) from France [ 25 ]. Based on the COI locus, an isolate of Australapatemon sp.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, a detailed molecular analysis of cercariae and adult specimens of Australapatemon sampled across North America clearly indicates the existence of several distinct lineages within this taxon and indisputably illustrates the hidden species diversity [ 13 , 15 ]. In Europe, Huguenin et al [ 25 ] identified another lineage within Australapatemon cercariae using Matrix-Assisted Laser Desorption-Ionisation–Time of Flight (MALDI-TOF) mass spectrometry, but the taxonomic position and molecular diversity of larval stages of Australapatemon collected from a wide range of intermediate hosts (snails and leeches) have not been the subject of extensive studies. The genetic variability and species richness within the genus Australapatemon from various geographical regions thus remain relatively unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The use of new low-cost and high throughput tools like MALDI-TOF MS [14] to detect such hybrids could be helpful to explore this challenge.…”
Section: Discussionmentioning
confidence: 99%
“…An essential feature of MALDI-TOF MS is that in addition to detecting bacteria, it can be used to detect microbial toxins [ 44 ], study antibiotic resistance [ 45 47 ], detect viruses [ 48 , 49 ], parasites [ 50 , 51 ], fungi [ 52 , 53 ], and study of human [ 54 56 ] and plant cells [ 57 , 58 ], which makes us more familiar with the creatures in our environment.…”
Section: The General Applications Of Maldi-tof Msmentioning
confidence: 99%